The Lives of Jessie Sampter : Queer, Disabled, Zionist - Imhoff, Sarah (Book collections on Project MUSE., 2022)
"Jessie Sampter (1883-1938) was best known for her 95-page A Course on Zionism, an American primer for understanding support of a Jewish state in Palestine first published in 1915. In 1919, Jessie packed a trousseau, and declared herself "married to Palestine." Yet Sampter's own life and body hardly matched typical Zionist ideals: while Zionism celebrated the strong and healthy body, Sampter spoke of herself as "crippled" from polio and plagued by weakness and sickness her whole life; while Zionism applauded reproductive women's bodies, Sampter never married or bore children. In fact, she wrote of homoerotic longings and had same-sex relationships we would consider queer. Though Jessie Sampter was in many ways quite distinctive, analyzing her life illuminates a sometimes invisible aspect of the human condition: our embodied selves do not always neatly line up with our religious or political ideals. In its telling of the lives of Sampter, the book pursues an embodied method of learning about the past. It draws not only on texts and material objects-the things scholars usually interpret through reading and seeing-but also what we apprehend by other senses, feelings, and experiences"--